Investment Prospects in Renewable Energy in North Africa - Jumia O. A. Madi; Abdulsalam M. A. Altarhouni; Muftah Faraj (Journal of Scientific and Human Dimensions, 2026)
Africa is a continent with much diversity and untapped potential, with the northern part being among the most well-endowed areas when considering natural resources. A considerable part of North Africa is occupied by the Sahara and hence enjoys a substantial amount of sunlight and gets some of the globe’s strongest winds. Such features make this part of Africa the most acknowledged in terms of natural resources. The sunny Northern African nations, like Morocco, Egypt, Tunisia, and Algeria, are not only shifting towards, and in fact adopting, renewable energy as part of their economic diversification goals, but are also striving for sustainability. The cost of technology has gone down, and due to favorable climatic conditions in the region, the production of renewable energy has increased monumentally over the past decade in solar and wind energy. Investment attraction has been a key role of government policies and regulations. The governments of North African nations have adopted different tax measures, including investment legislation, tax funds for renewable energies, and feed-in tariffs to encourage domestic and foreign investors. The impact of such policies includes an increase in the portion of renewable energy in the country while decreasing reliance on energy imports and fossil fuels. There are several economic benefits of renewable energy investments in North Africa, such as economic development, job creation, technological advancement, energy security, and environmental sustainability. It likewise places North Africa as a possible center for green hydrogen generation because of the inexpensive renewable resources. The industry, though, still faces several monumental challenges, such as poor infrastructure, inadequate capability of transmission lines, lack of regulatory clarity, shortage of resources, and a workforce with the necessary skills to solve the challenges in the future. Nevertheless, the future is encouraging; should there be governments, there is a strengthening of structures, infrastructure, and international collaboration